Tunable Neel-Bloch Magnetic Twists in Fe3GeTe2 with van der Waals Structure - Peng, Licong; Yasin, Fehmi S.; Park, Tae-Eon; Kim, Sung Jong; Zhang, Xichao; Nagai, Takuro; Kimoto, Koji; Woo, Seonghoon; Yu, Xiuzhen (WILEY-V C H VERLAG GMBH, 2021)
The advent of ferromagnetism in 2D van der Waals (vdW) magnets has stimulated high interest in exploring topological magnetic textures, such as skyrmions for use in future skyrmion-based spintronic devices. To engineer skyrmions in vdW magnets by transforming Bloch-type magnetic bubbles into Neel-type skyrmions, a heavy metal/vdW magnetic thin film heterostructure has been made to induce interfacial Dzyaloshinskii-Moriya interaction (DMI). However, the unambiguous identification of the magnetic textures inherent to vdW magnets, for example, whether the magnetic twists (skyrmions/domain walls) are Neel- or Bloch-type, is unclear. Here we demonstrate that the magnetic twists can be tuned between Neel and Bloch-type in the vdW magnet Fe3GeTe2 (FGT) with/without interfacial DMI. We use an in-plane magnetic field to align the modulation wavevector q of the magnetizations in order to distinguish the Neel- or Bloch-type magnetic twists. We observe that q is perpendicular to the in-plane field in the heterostructure (Pt/oxidized-FGT/FGT/oxidized-FGT), while q aligns at a rotated angle with respect to the field direction in the FGT thin plate thinned from bulk. We find that the aligned domain wall twists hold fan-like modulations, coinciding qualitatively with our computational results.